Dampak quarter life crisis terhadap perencanaan karier mahasiswa psikologi: telaah konseptual - Raffi, Muhammad Haidar (Maliki Interdisciplinary Journal, 2025)
Quarter life crisis (QLC) is a common phenomenon experienced by early adulthood students and significantly influences their career planning process. This phase is marked by confusion, identity crisis, and future uncertainty that can decrease students’ self-confidence. This article aims to explain the impact of QLC on the career planning of psychology students using a conceptual approach based on literature. Previous research shows that students experiencing QLC tend to face obstacles in deciding career directions and making professional decisions. This article also outlines various strategies students can implement to maintain a clear career plan despite the crisis. These strategies include self-reflection, career counseling, participation in self-development activities, and social support. By understanding the dynamics of QLC, it is hoped that students can turn this phase into a growth opportunity toward a more well-planned future.